Data Literacy: Perception and degree of satisfaction among university students - Martín González, Yolanda; Travieso Rodríguez, Críspulo; Toro Pascua, José C.; Iglesias Rodríguez, Ana; Hernández Martín, Azucena (Revista General de Información y Documentación, 2023)
This article presents the results obtained from a study carried out within the framework of a Teaching Innovation Project on data literacy, developed in five undergraduate degrees at the University of Salamanca, with the aim of finding out the perception and degree of satisfaction of university students with respect to the search and retrieval of open data. The non-experimental quantitative methodological approach was applied, using statistical, descriptive and inferential techniques. A sample selection has been made by availability, accessing 310 students from the branches of knowledge Social and Legal Sciences, and Arts and Humanities. The data collection instrument was a questionnaire made up of closed and open-ended questions, referring to the variables to be studied. The results obtained made it possible to identify the difficulties encountered by the students in terms of choosing the source of data, carrying out the information search process and understanding the datasets. They also show how the students value positively the training in data and its usefulness in the learning of other subjects, as well as in their professional life. The study has obtained empirical evidence about the level of perception and satisfaction that undergraduate students have regarding data literacy. It has also exposed the need to incorporate this transversal competence in university education and to promote the, so far, limited research on the potential use of open data in learning.
Keywords: Data literacy; Higher education; Information literacy; Undergraduate student; Digital skills